A coral-rich unit of Berriasian (Early Cretaceous) age in the Sierra Madre Oriental of northeastern Mexico. (August 2016) - Zell, Patrick; Stinnesbeck, Wolfgang; Hering, Fabio
Abstract: A coral-rich Berriasian unit locally known as the San Juan Lentil conforms the basal Taraises Formation in the San Juan canyon located half distance between the cities of Saltillo and Monterrey in northeastern Mexico. Here we document the environmental conditions and discuss its regional distribution of this biostrome unit. Calpionellids are intermittently present and indicate a middle to late Berriasian age for the coral-bearing unit that was deposited during an interval of increased oligotrophic conditions. Highlights: We provide data about stratigraphy and depositional environments of coral bearing strata from northeastern Mexico. Our results indicate a Berriasian age for the corals. Corals were deposited during an interval of increased oligotrophic conditions.